El estatuto de refugiado erigido como frontera humanitaria en Chile - Martina Cociña-Cholaky; Nanette Liberona Concha (Colombia Internacional)
Objective/context: This study analyzes how Chile has handled the granting of asylum from 2010 to the present, effectively transforming it into an exception. This situation has intensified amid increasing regional forced mobility due to various barriers to accessing the asylum application process and requirements imposed by regulatory changes aligned with migration governance policies. By employing the notion of a humanitarian frontier, the study examines processes of selectivity and differentiation marked by affiliation with certain nationalities. Methodology: A mixed qualitative analysis was conducted, including statistical review, document analysis, and examination of management practices related to forced displacement. The study explores two cases that illustrate how the state has restricted the recognition of asylum. Conclusions: The findings reveal that Chile employs selective state management differentiated by nationality, prioritizing the protection of certain migrant groups that align with the classical definition of a refugee. This approach is linked to the non-recognition of other diasporas experiencing forced mobility. Originality: This paper examines the state of asylum in Chile by connecting it to the concept of a humanitarian frontier, aiming to reveal how state protection intertwines with the control of mobility.